2006
DOI: 10.1177/002204260603600309
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Alabama Students from Alcohol and Drugs: A Multi-Level Modeling Approach

Abstract: This research examines both risk and protective factors in the frequency of drug and alcohol use by Alabama public school students in grades six through 12. Factors are measured at the individual and county level. The data on both levels were obtained by the Substance Abuse Services Division of the Alabama Department of Mental Health and Mental Retardation. The results of data analysis—comprising hierarchical linear modeling techniques (HLM)—show that, overall, the individual protective factors do reduce stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 60 publications
1
22
1
Order By: Relevance
“…Race is important to consider in light of the race-specific challenges that African-Americans face in terms of substance abuse exposure and recovery (Brown, 2006). Sex was included because males have been associated with higher levels of substance abuse and other criminal/deviant behaviors than females (Lo, Anderson, Minugh, & Lomuto, 2006). The bonding variables measured an individual's stake in their families and communities and served as preventative measures against deviant behaviors such as substance abuse.…”
Section: Spirituality Self and Substance Abusementioning
confidence: 99%
“…Race is important to consider in light of the race-specific challenges that African-Americans face in terms of substance abuse exposure and recovery (Brown, 2006). Sex was included because males have been associated with higher levels of substance abuse and other criminal/deviant behaviors than females (Lo, Anderson, Minugh, & Lomuto, 2006). The bonding variables measured an individual's stake in their families and communities and served as preventative measures against deviant behaviors such as substance abuse.…”
Section: Spirituality Self and Substance Abusementioning
confidence: 99%
“…Two variables were used to assess the frequency of alcohol use over lifetime and frequency of alcohol use past 30 days. The research study provided evidence that strong family ties did offer protection against the use of alcohol and other drugs [5]. In a separate study, students from a sample of undergraduate students were almost 1.5 times likely to abstain from alcohol if their mother abstained from alcohol as those whose mother was a drinker [6].…”
Section: Cultural Influences and Family Valuesmentioning
confidence: 90%
“…Lo et al, [5], surveyed 98,822 students in Alabama that were enrolled for the 2002 spring term. Two variables were used to assess the frequency of alcohol use over lifetime and frequency of alcohol use past 30 days.…”
Section: Cultural Influences and Family Valuesmentioning
confidence: 99%
“…Surprisingly, they found that neighborhood disadvantage was associated with decreased frequency of alcohol, marijuana, and other drug use among these students. Moreover, the effects of both protective and risk factors were reduced for students living in disadvantaged neighborhoods (Lo et al, 2006). Snedker et al's (2009) findings were similarly inconsistent with the social disorganization theory.…”
Section: Neighborhood Disadvantage and Substance Usementioning
confidence: 96%
“…These studies found that neighborhood context affected the strength of individual protective and risk factors for adolescent alcohol use (Chuang et al, 2009;Snedker et al, 2009). Lo, Anderson, Minugh, and Lomuto (2006) examined protective and risk factors for the frequency of drug and alcohol use in a sample of nearly 93,000 middle-and high-school students in Alabama. Surprisingly, they found that neighborhood disadvantage was associated with decreased frequency of alcohol, marijuana, and other drug use among these students.…”
Section: Neighborhood Disadvantage and Substance Usementioning
confidence: 99%